Cross-Culture Adaptation and Validation of Indonesian version of CRAFFT Substance Abuse Screening Test among adolescents - Mohd Nazri Bin Mohd Daud; Noor Hassline Binti Mohamed; Azman Bin Atil; Linlin Lindayani; Tuty Yanuarti (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Substance abuse among adolescent in Indonesia remains public health problem. The CRFFT is the most widely utilized high-risk drug screening tool. Its use in different countries and contexts shows its enormous potential. Although the CRAFFT has been utilized on occasion by professionals and researchers in Indonesia, no psychometric tests have been conducted to ensure that it works reliably in our country. Objectives: This study aimed to examine the psychometric performance of the CRAFFT screening tool among Indonesian adolescents. Methods: Eighty adolescents aged 15–18 years, recruited from a drug rehabilitation facility in West Java, Indonesia, participated in the research. The CRAFFT instrument underwent a four-step translation and adaptation process. Content validity was assessed using Aiken’s V index. The factorial structure of the instrument was explored through exploratory factor analysis (EFA) and subsequently verified with confirmatory factor analysis (CFA). Internal consistency reliability was evaluated using the Kuder–Richardson 20 (KR-20) coefficient. Results: CRAFTT CVI was 0.80–1.00 with the factor loadings for each of the three scales in the CRAFTT was 0.65–0.88. The results of the confirmatory factor analysis (CFA) for CRAFFT were as follows: I2 = 64.11, p-value = 0.121, and df = 78. Pearson correlation coefficients for the six different subscales ranged from 0.450 to 0.637. KR-20 coefficient of CRAFFT was 0.767. Corrected Homogeneity Index (CHI) ranged from 0.314 to 0.580. Conclusion: The results of this study demonstrate that the CRAFFT instrument can serve as a practical and effective tool for identifying substance use issues among adolescents in Indonesia. Further investigations are recommended to examine its sensitivity and specificity in order to establish stronger evidence for the validity of the CRAFFT within this population.